PS-031 Pharmaceutical interventions performed in a short stay emergency service. (25th February 2017) - Trias, L Borràs; Sureda, M Florit; García-Peláez, M; Comas, G Puig; Albors, P Miralles; Torner, MQ Gorgas
Abstract : Background: One of the objectives of the Health Department of Catalonia (Spain) is the clinical review of medications in chronic complex patients (CCP) and patients with advanced disease (PAD). The reconciliation and validation of treatments to detect and prevent drug related problems (DRPs) in a short stay emergency service (SSES) is among the functions of the hospital pharmacist. Purpose: To describe the pharmaceutical interventions (PI) implemented in an SSES and their degree of acceptance by the physician, and to analyse PI according to the type of patient (CCP, PAD and others). Material and methods: A retrospective, descriptive, observational study of data retrieved from January to August 2016 was conducted. Interventions performed by a pharmacist in SSES (20 beds) from Monday to Friday were recorded and communicated to the responsible prescriber. Data collected: class of patient, type of PI and acceptance of the recommendation by the prescriber. Results: A total of 344 PI in 248 patients were registered: 14 PI in 8 PAD, 95 in 66 CCP and 235 in 174 others. The degree of acceptance of PI were: 79.9% accepted, 6.7% rejected and 13.4% not evaluated due to the discharge of the patient before resolution of the PI. The PI most frequently performed were: 36.6% detection of omission of chronic treatments (65.9% accepted, 7.9% rejected, 26.2% not evaluated), 20.1% therapeutic equivalent switching (98.6% accepted, 1.4% rejected), 16.3% safety monitoring recommendations (96.4% accepted, 3.6% rejected) and 7.3% dosage adjustment (72% accepted, 16% rejected, 12% not evaluated). The most frequent PI in PAD were 35.7% therapeutic equivalent switching and 28.6% detection of omission of chronic treatments, while for CCP the most frequent PI were 47.4% detection of omission of chronic treatments, 14.7% safety monitoring recommendations, 7.4% renal dose adjustment and 7.4% therapeutic equivalent switching. For other patients, 32.8% were detection of omission of chronic treatment, 24.3% therapeutic equivalent switching and 17.4% safety monitoring recommendations. Conclusion: Detection of omission of chronic treatments was the most frequent PI recorded. The degree of acceptance of the PI by the prescriber was high. The interventions performed by the pharmacist in the SSES are key to prevent DRPs. References and/or acknowledgements: Programa de prevenció i atenció a la cronicitat de Catalunya 2011–2014 (PPAC). Health-Department. Government of Catalonia. No conflict of interest